Anthropological invariants in travel behavior - Marchetti, C. (Technological forecasting and social change)
Personal travel appears to be much more under the control of basic instincts than of economic drives. This may be the reason for the systematic mismatch between the results of cost benefit analysis and the actual behavior of travelers. In this paper we put together a list of the basic instincts that drive and contain travelers' behavior, showing how they mesh with technological progress and economic constraints.